Parametric analysis of the stability of a bicycle taking into account geometrical, mass and compliance properties. (2017) - Doria, Alberto; Favaron, Valerio; Taraborrelli, Luca; Roa, Sergio
Some studies of bicycle dynamics have applied the Whipple Carvallo bicycle model (WCBM) for the stability analysis. The WCBM is limited, since structural elements are assumed to be rigid bodies. In this paper, the WCBM is extended to include the front assembly lateral compliance, and analysis focuses on the study of the open loop stability of a benchmark bicycle. Experimental tests to identify fork and wheel properties are performed, this data is used in the stability analysis for ranking the influence of design parameters. Indexes from the eigenvalues analysis are applied in a full factorial approach. The results show that introducing front assembly compliance generates a wobble mode with little effect on self-stability. The forward displacement of the centre of mass of the rear frame and the increment in trail lead to large increments in the self-stability, whereas increments in front wheel radius and wheelbase reduce stability.